2020
DOI: 10.1037/pas0000941
|View full text |Cite
|
Sign up to set email alerts
|

Examining the “traditional background hypothesis” for the MMPI-2–RF L-r scores in a Muslim faith–based sample.

Abstract: The traditional background hypothesis (TBH) is a long-standing belief associated with the Minnesota Multiphasic Personality Inventory (MMPI) L scale; a validity scale, which appears on every version of the family of MMPI instruments including the soon-to-be released MMPI-3. The L scale was originally designed to assess whether test respondents presented themselves in an unrealistically favorable light. Both researchers and clinicians noted, however, that those from traditional Christian faith–based groups prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Likewise, the studies identified in this systematic review demonstrated stronger accuracy in identifying symptom exaggeration, as effect sizes for minimization were substantially smaller. This may also reflect cultural influences, as individuals from some cultures may have response patterns that typically correspond to minimization, making these scales less effective in differentiating deliberate symptom minimization from culturally normative responding (Bagby et al, 2020;Friedman et al, 2001). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the studies identified in this systematic review demonstrated stronger accuracy in identifying symptom exaggeration, as effect sizes for minimization were substantially smaller. This may also reflect cultural influences, as individuals from some cultures may have response patterns that typically correspond to minimization, making these scales less effective in differentiating deliberate symptom minimization from culturally normative responding (Bagby et al, 2020;Friedman et al, 2001). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 99%